Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24043136
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies: The Greatest Resource to Treat Multiple Myeloma

Abstract: Multiple myeloma (MM) is a currently incurable hematologic cancer. This disease is characterized by immunological alterations of myeloid cells and lymphocytes. The first-line therapy involves the use of classic chemotherapy; however, many patients have a relapsed form that could evolve into a refractory MM. The new therapeutic frontiers involve the use of new monoclonal antibodies (Mab) such as daratumumab, isatuximab, and elotuzumab. In addition to monoclonal antibodies, new immunotherapies based on modern bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…CD38 is a prime target in MM, with two anti-CD38 mAbs (Daratumumab and Isatuximab) currently approved for use in the United States. These immunotherapeutic agents have transformed the treatment of MM, with a diverse mechanism of action composed of antibody-dependent, cell-mediated cytotoxicity, antibody-dependent cellular phagocytosis, and complement-dependent cytotoxicity [53][54][55][56]. While CD38 has exhibited susceptibility to immunoediting as a consequence of selective pressure imposed by immunotherapeutic agents [57], we have deliberately chosen to target it.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 is a prime target in MM, with two anti-CD38 mAbs (Daratumumab and Isatuximab) currently approved for use in the United States. These immunotherapeutic agents have transformed the treatment of MM, with a diverse mechanism of action composed of antibody-dependent, cell-mediated cytotoxicity, antibody-dependent cellular phagocytosis, and complement-dependent cytotoxicity [53][54][55][56]. While CD38 has exhibited susceptibility to immunoediting as a consequence of selective pressure imposed by immunotherapeutic agents [57], we have deliberately chosen to target it.…”
Section: Discussionmentioning
confidence: 99%
“…LT1100; Fenton, MO). [N- (3,11,14,22,25,10,15,21,26,32-hexaaza-10,21,32-trihydroxytetratriacontane)]-maleimide (deferoxamine-maleimide) was sourced from Macrocyclics (Dallas, TX). Finally, phorbol 12-myristate 13acetate and Tris(2-carboxyethyl) phosphine hydrochloride (TCEP) were sourced from Sigma-Aldrich (St. Louis, MO).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In MM, the ability of bortezomib (BTZ) to overcome CAM-DR was in part due to VLA4 downregulation. 9 A more practical approach to disable VLA4 in hematopoietic malignancies is to induce target-specific immune responses with antibody (Ab) therapeutics, 10 which offer added strengths of low toxicity and off-the-shelf availability. The application of Ab therapeutics against VLA-4 for leukemia and MM is highly plausible due to its participation in chemotherapy resistance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In vitro models showed that sBCMA reduces the cytotoxic effects of BCMA-directed CARs in a dose-dependent manner; notably, no cell lysis occurred at sBCMA levels of 2343 ng/mL [27]. Given the importance of BCMA in MM physiology and its almost unique expression on malignant PCs, numerous therapies have been introduced targeting this specific molecule, including conjugate antibodies (Belantamab mafodotin) and bispecific antibodies (Teclistamab and Elranatamab) [28].…”
Section: Bcma-targeting Car-tmentioning
confidence: 99%